2011
DOI: 10.1073/pnas.1010666108
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the near-24-hour intrinsic period of the human circadian timing system

Abstract: The circadian rhythms of melatonin and body temperature are set to an earlier hour in women than in men, even when the women and men maintain nearly identical and consistent bedtimes and wake times. Moreover, women tend to wake up earlier than men and exhibit a greater preference for morning activities than men. Although the neurobiological mechanism underlying this sex difference in circadian alignment is unknown, multiple studies in nonhuman animals have demonstrated a sex difference in circadian period that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
369
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 489 publications
(403 citation statements)
references
References 62 publications
26
369
4
4
Order By: Relevance
“…Nevertheless, it should be noted that our sample size is smaller than in these studies, which could have prevented us from detecting between-sex differences. Similar to current findings, a subsequent study using a forced desynchrony protocol also failed to detect a statistically significant sex difference in the circadian phase of melatonin secretion (12). Our prior controlled study found no menstrual phase difference in the circadian melatonin profile (13), although there have been other reports of decreases (30), increases (31), phase delays (32), or no change (29) in melatonin secretion during the luteal vs. follicular phase.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Nevertheless, it should be noted that our sample size is smaller than in these studies, which could have prevented us from detecting between-sex differences. Similar to current findings, a subsequent study using a forced desynchrony protocol also failed to detect a statistically significant sex difference in the circadian phase of melatonin secretion (12). Our prior controlled study found no menstrual phase difference in the circadian melatonin profile (13), although there have been other reports of decreases (30), increases (31), phase delays (32), or no change (29) in melatonin secretion during the luteal vs. follicular phase.…”
Section: Discussionsupporting
confidence: 64%
“…Duffy et al also reported that women have a shorter intrinsic circadian period of CBT and melatonin vs. men (12), which might contribute to these observations. Unfortunately, many prior studies that documented sex differences in circadian physiology have not done so while controlling for menstrual cycle and hormonal contraceptive use in female participants.…”
mentioning
confidence: 88%
“…Sex differences exist in the circadian timing of sleep; women tend to go to bed earlier and wake up earlier than men [32,49,50]. Retrospective analyses of the circadian timing system in men and women with similar sleep times and durations find that women have an early timing of circadian rhythms, particularly for endogenous temperature and melatonin [51], partly as a consequence of a significantly shorter circadian period [52]. Together, these studies suggest that circadian timing in women is even earlier than the sex difference in sleep timing would predict.…”
Section: Clinical Perspective (A) Sex Differences In Sleepmentioning
confidence: 99%
“…Such finding of a sex difference in intrinsic circadian period are consistent with studies conducted in a number of nonhuman animals that have demonstrated that circadian period is shorter in females than in males. The shorter intrinsic circadian period described in women may be attributable, partly, to the higher circulating levels of estrogen in women (29). In addition, exposure to high estrogen at some point during development could alter the hypothalamic circadian pacemaker, leading to the sexual dimorphism that has been reported in suprachiasmatic nucleus structure (30).…”
Section: -Sulfatoxymelatonin In Gh Deficient Adultsmentioning
confidence: 99%